Coronavirus Research Trends: A 50–Year Bibliometric Assessment. Issue 2 (2nd April 2020) - Ram, Shri
ABSTRACT: Coronaviruses (CoVs) are a large family of viruses and are endemic in humans and animals, causing respiratory and intestinal infections. Coronavirus has become a challenge in China region due to its recent outbreak at the start of the year 2020. The current outbreak of coronavirus disease (COVID) has resulted in many fatalities and has forced the people of Wuhan Province in China to remain confined in their homes. Two other two forms of CoV were epidemic in 2003 when Severe Acute Respiratory Syndrome (SARS-CoV) spread in Hong Kong and Middle East Respiratory Syndrome (MERS-CoV) spread in the Middle East region. This bibliometric study is an attempt to trace the trends of research associated with "Coronavirus" for a period of 50 years using the SCOPUS database. The study was carried out using the keyword Coronavirus and analyzed for annual growth, productive countries, institutes, authors, journals, highly cited papers, and research focus using keywords. There were two peaks when a large number of publications appeared. Most of the research publications were from the USA (31.67%), and the University of Hong Kong was the most productive institute. The Journal of Virology has published the most number of articles on CoV.